2021
DOI: 10.3389/fonc.2021.753209
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Hypofractionated With Conventional Fractionated Radiotherapy After Breast-Conserving Surgery for Early Breast Cancer: A Meta-Analysis of Randomized Controlled Trials

Abstract: BackgroundThe purpose of this meta-analysis was to compare the safety and efficacy between hypofractionated and conventional fractionation radiotherapy in patients with early-stage breast cancer after breast-conserving surgery.MethodsWe conducted a comprehensive search of PubMed, Embase, Web of Science, and the Cochrane Library to identify relevant randomized controlled trials (RCTs) published before February 2021. At the same time, the hazard ratio (HR), risk ratio (RR), and 95% confidence interval (CI) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…The results of this study showed that the metabolism of the mammary glands gradually decreased over 5 years after irradiation, and it became significantly lower than that before irradiation. Although there have been reports of breast atrophy and lactation disorders after irradiation [2,3], this is the first report of quantitative evaluation of metabolic changes in the mammary gland after irradiation. Pathological changes in the mammary gland after irradiation have been reported as epithelial atrophy, fat necrosis, fibrosis of terminal duct lobular unit, and fibroblastic intimal thickening of arteries and veins of various sizes [4][5][6].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The results of this study showed that the metabolism of the mammary glands gradually decreased over 5 years after irradiation, and it became significantly lower than that before irradiation. Although there have been reports of breast atrophy and lactation disorders after irradiation [2,3], this is the first report of quantitative evaluation of metabolic changes in the mammary gland after irradiation. Pathological changes in the mammary gland after irradiation have been reported as epithelial atrophy, fat necrosis, fibrosis of terminal duct lobular unit, and fibroblastic intimal thickening of arteries and veins of various sizes [4][5][6].…”
Section: Discussionmentioning
confidence: 86%
“…Adjuvant whole-breast irradiation (WBI) after lumpectomy has been the standard treatment for most patients with early-stage breast cancer [1]. Severe toxicity after WBI is rare, but moderate late adverse events such as induration, edema, breast atrophy have been reported [2]. Radiation therapy is known to impair lactation by reducing the metabolism and function of the mammary glands [3].…”
Section: Introductionmentioning
confidence: 99%
“…The study on efficacy encompassed three metrics, namely LR, OS, and DFS. Before this study, three meta-analyses reported on pooled LR and OS [ 57 59 ]. The results of our research align with their findings, indicating that there were no notable disparities between the two treatment protocols regarding LR and OS outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The search we performed in this paper was thorough and the studies we considered featured high-quality RCTs and retrospective investigations, which enhanced the dependability of the results. Compared to prior meta-analyses on the same topic [ 57 59 ], our sample size and the research measures for side effects were larger, and we included ductal carcinoma in situ (DCIS) patients for the first time. Specifically, the sample size of Andrade et al [ 59 ]was restricted to six studies, while the study conducted by Zhou et al .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is intensely discussed how the differently fractionated regimens of radiotherapy affect the outcome both in efficiency and toxicity. Some follow-up studies and meta-analyses have shown that the outcome of HypoRT could be compared to NormRT in efficiency, while other studies assume toxicity and side effects as fibrosis (14)(15)(16)(17)(18). HypoRT could potentially increase the patient's satisfaction and compliance by reducing the amount of treatments needed while reducing costs for the health care system for shorter therapeutic periods and therefore allowing the treatment of more patients (19,20).…”
Section: Introductionmentioning
confidence: 99%